PENGEMBANGAN METODE ISOLASI DNA GENOM PADA TANAMAN JARAK PAGAR (JATROPHA CURCAS) - Maftuchah, Agus Zainudin (Jurnal Gamma, 2006)
Molecular markers have been used extensively to study genetic relationships in number of crops.  One of the techniques that can be used to obtain DNA finger print is RAPD (random amplified polymorphic DNA) technique, a molecular technique based on PCR technology. The quality of amplification products depend on several factors such as MgCl2 concentration, primers, PCR condition and DNA quality. In this study, an experiment  was conducted to find out appropriate DNA isolation technique for three accessions Jatropha curcas (Karangtengah, Lamongan and NTB). Three DNA isolation technique has been tested  and two of them were able to produce good quality of genomic DNA. The results therefore indicate that the technique can be used to genomic DNA isolation of Jatropha curcas on molecular analysis.